2009
DOI: 10.1016/j.neuropsychologia.2009.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between recognition and recall in developmental amnesia

Abstract: Developmental amnesia (DA) is a memory disorder due to hypoxia/ischaemia-induced damage to the hippocampus early in life. To test the hypothesis that this disorder is associated with a disproportionate impairment in recall vis-à-vis recognition, we examined a group of 10 patients with DA on the Doors and People test, which affords a quantitative comparison between measures of the two memory processes. The results supported the hypothesis in that the patients showed a sharp, though not complete, recall-recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
51
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 28 publications
8
51
1
2
Order By: Relevance
“…Previous reports using the D&P test had already indicated a selective effect of hippocampal damage on recall (7)(8)(9)(19)(20)(21)(22), but those studies did not examine whether this selective mnemonic effect was correlated with extent of hippocampal damage. Because our patient cohort was a large one and had wide variation in extent of hippocampal atrophy, we were able to examine this structure/function relationship and found a sharp distinction between recall and recognition performance, with only the former showing a correlation with extent of HV loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports using the D&P test had already indicated a selective effect of hippocampal damage on recall (7)(8)(9)(19)(20)(21)(22), but those studies did not examine whether this selective mnemonic effect was correlated with extent of hippocampal damage. Because our patient cohort was a large one and had wide variation in extent of hippocampal atrophy, we were able to examine this structure/function relationship and found a sharp distinction between recall and recognition performance, with only the former showing a correlation with extent of HV loss.…”
Section: Discussionmentioning
confidence: 99%
“…The D&P test was administered to all participants according to the instructions in the published manual (10) and as described in detail in ref. 9. The test consists of four subtests, two assessing recognition and two assessing recall, and, within each of these pairs, one assessing visual ability and the other, verbal ability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of developmental as well as adult-onset amnesia have reported cases in which hippocampal damage produced intact recognition memory but impaired episodic memory, or the ability to recollect information pertaining to the specific event during which the stimulus was first encountered (11,12,15,18, but see also 6). The "RememberKnow" procedure has often been used to try to distinguish impairments in simple recognition from deficits in recall (12,15,(19)(20)(21).…”
mentioning
confidence: 99%
“…Behavioural similarities in ASD and parietal patients in the areas of memory (Adlam et al, 2009;Berryhill et al, 2010;Davidson et al, 2008;Drowos et al, 2010) and attention (Behrmann et al, 2004;Han et al, 2004;Malhotra et al, 2009) have led to the parietal lobes being advocated as contributors to the observed behavioural difficulties in ASD (Boucher and Mayes, 2012;Maister et al, 2013). In addition, rats with hippocampal and parietal lesions showed close to chance structural learning (Aggleton et al, 2007;Sanderson, 2005).…”
Section: Discussionmentioning
confidence: 99%